ISLAMIC RELIGIOUS CONTENT ON INSTAGRAM REELS: BETWEEN EDUCATION AND ENTERTAINMENT - Iswahyudi Tejo Yuwono (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
This study explores the phenomenon of Islamic religious content on Instagram Reels, which has rapidly gained popularity as a medium that combines education and entertainment. The rise of short video formats on social media has encouraged preachers, educators, and Muslim content creators to disseminate religious values in ways that are more accessible and engaging to younger audiences. This research aims to analyze how Instagram Reels serves as a hybrid platform where Islamic teachings are not only conveyed through didactic messages but are also packaged in creative, humorous, and entertaining forms. By employing a qualitative approach, the study observes selected Islamic Reels content and examines audience perceptions regarding the balance between its educational value and entertainment appeal. The findings suggest that while the majority of viewers appreciate the creative packaging of religious messages, there remains a tension between maintaining the authenticity of Islamic teachings and adapting them into entertaining formats. For many users, Reels become a means of quick spiritual reflection in their daily routines, yet some also express concerns about oversimplification or trivialization of religious values. This research contributes to the growing discourse on digital religion and media convergence by highlighting the dual role of Instagram Reels as both a pedagogical tool and a source of leisure. Ultimately, the study underscores the importance of balancing da’wah effectiveness with ethical responsibility in producing Islamic content within the dynamic landscape of social media